Exploring the causes of selected conduct disorders among school-going adolescents in Uganda and South Africa - Kiiza, Kobusingye Loyce; Newlin, Marongwe (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study’s main issue was the causes of selected conduct disorders among adolescents in school. Adolescent conduct disorders emanate from a variety of factors that include social, economic, school, genetic status and parental factors. The purpose of the study was to explore the causes of selected conduct disorders among adolescents in school. The study was qualitative, explorative and phenomenological in nature. The study participants were parents and teachers. Data were collected using online (WhatsApp) focus group discussions due to restrictions brought about by COVID-19 that made physical interaction risky. Data were analysed in an integrative manner using findings from the two countries from parents and teachers, and thematically using themes generated from the outcomes of the online discussions. Findings indicate that conduct disorders among secondary school adolescents are a result of developmental, parental, school, social and academic factors. The study concludes that conduct disorders are recognised among the secondary school adolescents in Uganda and South Africa and pose a challenge to education and affect the proper functioning of schools. From the findings and conclusions, the researchers recommend hands-on parenting, adolescent psycho-social services, guidance and counseling services in schools, career guidance based on students’ needs, academic strengths and aspirations, positive peer groups and moderation of punishment at home and at school. This has implications on the need for dynamics in parenting, teacher-student relationships and psycho-social services that are detrimental in building healthy developmental milestones that have a direct impact on behavior and conduct among adolescents.